2010
DOI: 10.1038/jhh.2009.100
|View full text |Cite
|
Sign up to set email alerts
|

Total antioxidant status and oxidative DNA damage in a South Indian population of essential hypertensives

Abstract: To investigate the total antioxidant status (TAS) and the extent of oxidative DNA damage in total lymphocytes and their relation with essential hypertension. A total of 130 South Indian subjects aged 30-65 were recruited for the study. Of these hypertensive subjects investigated, 30 were newly diagnosed and were not on any antihypertensive drugs, but had systolic blood pressure (BP) ranging between 140 and 160 mm Hg and diastolic BP between 95 and 100 mm Hg; 50 hypertensive patients who were already on drug th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
7
12
0
Order By: Relevance
“…This finding is consistent with the findings of other studies [21,33]. Reduced total antioxidant status (TAS) in hypertensive subjects compared to normotensive subjects has also been reported by some studies [25,34]. On evaluating the protein carbonyl content, we found a higher oxidative stress in hypertensive subjects (Fig.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…This finding is consistent with the findings of other studies [21,33]. Reduced total antioxidant status (TAS) in hypertensive subjects compared to normotensive subjects has also been reported by some studies [25,34]. On evaluating the protein carbonyl content, we found a higher oxidative stress in hypertensive subjects (Fig.…”
Section: Discussionsupporting
confidence: 95%
“…ROS occurs more frequently in hypertensive subjects than in normotensives [23][24][25]. A recent study in Chinese Han adults showed that oxidative stress is a reliable risk factors for developing hypertension [26].…”
Section: Introductionmentioning
confidence: 98%
“…DNA damage and DNA repair seem to be closely associated with aging as a result of endogenous factors, lifestyle, occupational or environmental exposure [30]. Some atherosclerosisrelated diseases, whose pathogenesis involves both inflammation and oxidative stress, lead to DNA-damage induction [31] and could explain the higher basal DNA damage found in our study in patients and in matched controls [32].…”
Section: Discussionsupporting
confidence: 46%
“…Recently, antioxidant compounds such as luteolin, quercetin, rosmarinic acid, butin, and 7,8-dihydroxyflavone were shown to enhance oxidative DNA damage protection and repair (Silva et al 2008;Kang et al 2009;Zhang et al 2009a), suggesting these compounds may protect against oxidative stress-induced DNA damage, which occurs in several pathological conditions such as Alzheimer's disease, cancer, and hypertension (Zana et al 2006;Thompson 2006;Subash et al 2010).…”
mentioning
confidence: 99%